Pengembangan Sumber Daya Manusia dalam Meningkatkan Kinerja Guru di SMA Negeri 1 Waikabubak Kabupaten Sumba Barat - Ratu Linda Mentana Duil; Hendrik Toda; Yaherlof Foeh; Cataryn V. Adam (Jurnal Manajemen dan Ekonomi Kreatif, 2026)
Human resource development plays a strategic role in improving teacher performance and the quality of educational services. However, educational institutions in developing regions continue to face challenges related to teacher competency, unequal distribution of educators, limited access to professional development programs, and inadequate educational facilities. This study aims to analyze human resource development in improving teacher performance at SMA Negeri 1 Waikabubak, West Sumba Regency, through the dimensions of planning, education and training, and human resource management. The study employed a qualitative approach using a case study design. Data were collected through interviews, observations, and documentation involving the principal, vice principal, teachers, and parents. Data analysis was conducted using the interactive model of data reduction, data display, and conclusion drawing. The findings indicate that human resource development has been implemented through systematic planning processes, including human resource inventory, forecasting, and development planning based on school needs. Education and training programs have been carried out continuously through workshops, subject teacher forums, and in-house training activities, contributing to the improvement of teachers’ pedagogical and professional competencies, particularly in the utilization of educational technology. Furthermore, human resource management has been implemented through teacher placement, recruitment, maintenance, supervision, and performance evaluation, although several challenges remain, including shortages of teachers in specific subjects and limited supporting facilities. The study concludes that human resource development has contributed positively to improving teacher performance; however, further efforts are required to strengthen planning, expand professional development opportunities, and optimize educational support facilities to enhance educational quality sustainably.